2011
DOI: 10.1097/aln.0b013e318219524e
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic Ketamine Impairs Rats' Recall of Previous Information

Abstract: Background: There is poor experimental evidence concerning the effects of anesthetic doses of the noncompetitive N-methyl-D-aspartate receptor antagonist ketamine on rodents' memory abilities. The current study was designed (1) to investigate the consequences of posttraining administration of anesthetic ketamine (100 mg/kg intraperitoneally) on rats' recognition memory and (2) to evaluate the ability of the nitric oxide synthase inhibitor N-nitro-L-arginine methylester (L-NAME; 1, 3, and 10 mg/kg intraperitone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 35 publications
(55 reference statements)
3
7
0
Order By: Relevance
“…Zarate and Machado-Vieira ( 127 ) postulated that the ability of nitrous oxide to generate NO may be important in its antidepressant actions. Consistent with this, some synaptic and memory impairing effects of ketamine involve NO synthesis ( 78 , 128 ).…”
Section: Other Potential Mechanisms Of Nitrous Oxidesupporting
confidence: 54%
“…Zarate and Machado-Vieira ( 127 ) postulated that the ability of nitrous oxide to generate NO may be important in its antidepressant actions. Consistent with this, some synaptic and memory impairing effects of ketamine involve NO synthesis ( 78 , 128 ).…”
Section: Other Potential Mechanisms Of Nitrous Oxidesupporting
confidence: 54%
“…Neither CSDS nor acute ketamine affected locomotor activity, an important factor to rule out non-specific effects on gross motor output that can complicate data interpretation. Considering that ketamine produces amnestic effects in rodents (52,53), we assessed the possibility that ketamine interferes with stress-related learning and memory. Consistent with previous work (50), we found that 20 mg/kg ketamine does not interfere with performance in the passive avoidance test, suggesting that the antidepressant-like effects of the drug in our studies are not due to memory impairment.…”
Section: Discussionmentioning
confidence: 99%
“…While standard antidepressant treatments have delayed therapeutic efficacy (often several weeks), recent studies demonstrate that a single dose of ketamine can produce rapid (though transient) antidepressant responses in depressed patients (3137)—including patients that are treatment-resistant (32,34,38,39)—and antidepressant-like effects in numerous models of depression (4051). To determine if the therapeutic-like actions of ketamine are accompanied by amnestic (learning- and memory-disrupting) effects often associated with NMDA antagonists (52,53) or anxiolytic effects (43) we examined performance in the passive-avoidance and elevated plus maze (EPM) tests. As a way of evaluating whether it is possible to mitigate the effects of CSDS on ICSS, we included studies using ΔFosB-overexpressing mice, which are less sensitive (resilient) to CSDS (54).…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that although there is a temporal delay between ketamine administration and LTP inhibition, ketamine-induced metaplasticity shares at least some mechanisms with the acute LTP inhibition observed following other treatments that activate NMDARs (Zorumski and Izumi, 2012). Interestingly, NOS inhibitors have also been found to overcome memory impairment (Boultadakis and Pitsikas, 2010; 2011; Wass et al, 2006) and information processing defects (Palsson et al, 2010) by ketamine and other NMDAR channel blockers, and have antidepressant effects in rodent models (Doucet et al, 2012). Whether ketamine-induced metaplasticity shares other mechanisms with acute NMDA-mediated LTP inhibition, including calcium influx, serine phosphatases and p38 mitogen activated protein kinase (Izumi et al, 1992b; Izumi et al, 2008) remains to be determined.…”
Section: Discussionmentioning
confidence: 99%